An analysis of the key products of village development organizations in Chevron's alternative livelihood project : prospects for enterprise development growth - Sarkar, Cathy Bipasha (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.